Research of Parallel Processing Technology Based on Multi-Core - Li, Xiang; Li, Fei; Wang, Chang Hao (Applied Mechanics and Materials, 2012)
In this paper, five kinds of typical multi-core processers are compared from thread, cache, inter-core interconnect and etc. Two kinds of multi-core programming environments and some new programming languages are introduced. Thread-level speculation (TLS) and transactional memory (TM) are introduced to solve the problem of parallelization of sequential program. TLS automatically analyze and speculate the part of sequential process which can be parallel implement, and then automatically generate parallel code. TM systems provide an efficient and easy mechanism for parallel programming on multi-core processors. Typical TM likes TCC, UTM, LogTM, LogTM-SE and SigTM are introduced. Combined the TLS and TM can more effectively improve the sequential program running on the multi-core processors. Typical extended TM systems to support TLS likes TCC, TTM, PTT and STMlite are introduced.